Improvement of students’ communication skills through targeted training and the use of simulated patients in dental education—a prospective cohort study - Anna Bock; Nina Wagenknecht; Philipp Winnand; Marie Sophie Katz; Mark Ooms; Marius Heitzer; Frank Hölzle; Ali Modabber (BMC Medical Education)
Abstract Background Good communication between patients and practitioners is essential, especially during dental procedures, as these treatments are often associated with increased nervousness and anxiety. The aim of this study was to investigate, implement and evaluate a concept for communication skills training by using targeted training in combination with simulation patients in dental education. Methods Students (n = 34) were assigned to four small groups receiving targeted training consisting of two parts. A lecture about the theoretical basics of communication skills and two practical sessions with simulation patients. During this training, one of the students performed the conversation with the patient. Immediately after self-assessment was obtained, the simulation patient, the remaining students and the lecturer provided feedback. Additionally, anonymous surveys were administered to the students at the beginning of the semester, immediately after the training and at the end of the course. Results The students rated the learning of communication skills as important for later professional life at all times. After targeted training followed by subsequent use in simulated patients, there was a significant improvement in communication skills (p < 0.001). The number of open-ended questions asked to patients after attending the course significantly increased (p = 0.0245). The communication training was considered useful, especially in small groups. Conclusion The implementation of targeted training with subsequent use in simulated patients significantly contributed to the students’ improvement in communication skills. The concept offers a good opportunity to better prepare students for interaction with patients, both in their studies and in their upcoming professional lives.